Short‐term stress responses and recovery of giant kelp (Macrocystis pyrifera, Laminariales, Phaeophyceae) juvenile sporophytes to a simulated marine heatwave and nitrate scarcity1. Issue 5 (22nd July 2021) - Umanzor, Schery; Sandoval‐Gil, José; Sánchez‐Barredo, Mariana; Ladah, Lydia B.; Ramírez‐García, Mary‐Mar; Zertuche‐González, José Antonio
Abstract : The frequency of marine heatwaves (MHWs) is increasing due to climate change. Although seaweeds are resilient to environmental changes, an increasing body of evidence shows that rising sea surface temperatures have deleterious effects on temperate kelp species. However, information on the vulnerability of juvenile kelp to these stressors and their population stability is limited. This study summarizes findings on the ability of juvenile sporophytes of Macrocystis pyrifera to survive and recover from simulated MHW conditions (22°C, 5 d) in combination with nitrate limitation (<1 µM) by evaluating photosynthetic capacity, nitrate uptake, tissue composition, bio‐optical properties, and oxidative stress of single‐blade juvenile sporophytes (<20 cm). Temperature, nitrate availability, and their interaction had significant effects on the physiological status of juvenile sporophytes after the exposure and recovery periods. Overall, as expected, the photosynthetic capacity of juvenile sporophytes decreased with increased temperature and lower nitrate availability. Short‐term exposure to simulated MHWs resulted in oxidative damage and reduced growth. The termination of the experimental warming allowed partial recovery to control values, indicating high physiological resilience. However, the interaction of both high temperature and nitrate scarcity induced irreversible damage to their photosynthetic capacity, with an increase in compensation irradiance, highlighting potential limitations in the carbon balance of juvenile sporophytes.